Simulations of symcap and layered NIF experiments with top/bottom laser asymmetry to impose P1 drive on capsules. (May 2016) - Eder, D; Spears, B; Casey, D; Pak, A; Ma, T; Izumi, N; Pollock, B; Weber, C; Kritcher, A; Jones, O; Milovich, J; Town, R; et al.
Abstract: Integrated hohlraum/capsule post-shot simulation of the first full-scale cryogenic layered-DT experiment with top/bottom laser asymmetries of 8% is discussed. The imposed P1 Legendre mode drive on the capsule results in downward velocity of 85 ± 15 km/s as measured by neutron time of flight (NTOF) diagnostics and x-ray imagers, which is in excellent agreement with the calculated velocity of 87 km/s. The measured DT yield is approximately 30% less than the average of two comparable shots using the same 4 shock HiFoot pulse shape without drive asymmetry. The calculated DT yield of 5.0e15 is very close to the measured value of 4.86e15 for the shot with drive asymmetry, which implies that P1 effects dominate yield reduction. The neutron activation diagnostics (NADs) give clear indication of higher areal density in the direction of the north pole in excellent agreement with calculations. Integrated post-shot simulation of an earlier symcap (capsule with appropriate ablator thicknesses to act as a surrogate for an ignition capsule) experiment with laser asymmetries show that calculated neutron-wighted velocity is a strong function of capsule shape.